Thermo-Mechanical Behavior of Novel Wood Laminae-Thermoplastic Starch Biodegradable Composites With Thermal Energy Storage/Release Capability - Dorigato, Andrea; Fredi, Giulia; Pegoretti, Alessandro (Frontiers in Materials, 2019)
For the first time, multifunctional fully biodegradable composites combining structural and thermal energy storage/release capabilities were prepared and thermo-mechanically characterized. At this scope, thin beech laminae impregnated with a phase change material (PCM) represented by poly(ethylene glycol) (PEG) were interleaved with thin foils of thermoplastic starch (TPS) and consolidated by hot pressing. From scanning electron microscopy it was observed that a certain amount of PEG (about 11 wt% of the total laminate) remained entrapped within the wood pores, negatively affecting the interfacial adhesion between wood laminae and TPS foils. The presence of PEG stabilized in the wood laminae was confirmed by differential scanning calorimetry tests, in which a specific melting enthalpy of 27.4 J/g was detected with a melting peak at 55 °C. Wood permeation with PEG was responsible of an increase of the dynamic moduli E’ and E’’, as well as of the tensile and Charpy impact strength of the laminates. Therefore, this paper highlighted the possibility to develop multifunctional fully biodegradable composites capable to combine structural and thermal energy storage properties, in which the selected PCM positively contributed to the mechanical behaviour of the laminates.